Recent Developments in the Green Syntheses of Chalcogenide Based Semi-conductor Nanoparticles - Hussain K. Rabinal, Mohammad; M. Gunnagol, Raghu; M. Hodlur, Rajashree (Current Nanomaterials, 2016)
Background: Semiconductor nanocrystals, particularly metal-chalcogenides, being at the interface of chemistry, physics, biology and materials science, have fascinated researchers in the last few decades. These materials find attractive application perspectives in solar cells, low cost/large format microelectronics, optoelectronics, biological tags and so forth. Objective: The size-dependent band gap of these materials is well-known, widely studied and well appreciated. The shape, surface conditions of nanoparticles, band alignment and structural orientation of capping molecules are also equally important parameters in controlling the properties. Method: In this review, an attempt has been made to survey the recent work of green syntheses on metal-chalcogenide nanoparticles by different routes. The aqueous approach is an advantageous alternative to the conventionally used organometallic route, mainly due to its scalability, environmental friendliness, cost effectiveness and more importantly, the biocompatibility. Results: The synthetic protocols are being developed for tailoring the composition, size, shape and surface functionalization of these materials by aqueous route with an exceptionally high degree. An attempt has been made to compare the recently reported results of these materials that are mainly synthesized by greener approaches. Conclusion: The review summarizes general aqueous synthetic strategies to achieve high quality metal chalcogenides that are recently reported and finally, the future, perspectives of these materials are also discussed.
Keywords: metal chalcogenides